Dampak Perubahan Harga Karet Terhadap Kondisi Sosial Ekonomi Petani Karet Di Desa Ambukha Kecamatan Lolofitu Moi Kabupaten Nias Barat - Ilda Budi Lestari Waruwu; Zulkarnain Lubis (Universitas Medan Area, 2022)
Agriculture is an activity of cultivating plants that can be used for life and a process of maintaining plants and animals. North Sumatra Province is one of the provinces in Indonesia, which has great potential in developing the agricultural sector, one of which is the export commodity of Ambukha Village, Lolofitu Moi District, West Nias Regency. 154 KK. The purpose of this research is to determine the impact of changes in rubber prices on the socio-economic conditions of rubber farmers and sources of income for rubber farmers other than rubber in Ambukha Village, Lolofitu Moi District. The research method uses qualitative and quantitative, sampling is done by simple random sample, the sample in this study is rubber farmers who have been selected. The data collected in this study are primary and secondary. Methods of data collection using questionnaires, interviews, and field observations. The results showed that the decline in rubber prices greatly affected the social conditions of rubber farmers and the amount of income other than rubber could not cover the lack of income of rubber farmers in Ambukha Village, Lolofitu Moi District, West Nias Regency.